Postwall German cinema : history, film history, and cinephilia - Frey, Mattias (Film Europa., 2013)
Since the fall of the Berlin Wall, there has been a proliferation of German historical films. These productions have earned prestigious awards and scored at box offices both at home and abroad, where they count among the most popular German films of all time. Suddenly, however, a significant departure has been made from the country's prominent cinematic take on history: the radical style, content, and politics of the New German Cinema. With in-depth analyses of the major trends and films, this book represents a comprehensive assessment of the historical film in postwall Germany.